Proceso de atención de enfermería en lactante de 1 mes con neumonía adquirida en la comunidad. - Aldaz Almeida, Romina Shelzea (2021)
Community-acquired pneumonia, also known by its acronym as CAP, is an acute condition of infectious origin that affects the lung parenchyma (GPC, 2017). Having said the following, a 1-month-old infant who comes in the company of her mother, for presenting generalized cyanosis that increases more when crying, dyspnea and hyperthermia of 38.5ºC. Immediately, vital signs were taken where it was evidenced: BP: 90 / 58mmHg, HR: 120Ixmin, FR: 30X`, Tº: 38.5ºC, Weight 3.3Kg, SATO2: 67% without oxygen, with oxygen 95% 2lt and size 43cm. Area doctor orders hematic biometry, urinalysis and stool tests. Patient is hospitalized and transferred to the Neonatal Intensive Care Unit area for follow-up and control. The following clinical case study in a 1-month-old infant who was diagnosed with community-acquired pneumonia, aims to apply the Nursing Care Process in conjunction with the Nanda, Nic and Noc taxonomy that was worked on the basis of the dysfunctional patterns that affect the health of the patient. Which were treated in conjunction with the appropriate treatment, in order to combat the infection and restore the quality of life of the patient.